2019
DOI: 10.3892/ol.2019.10207
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs aid the assessment of programmed death ligand�1 expression in patients with non‑small cell lung cancer

Abstract: The qualification of patients with non-small cell lung cancer (NSCLC) for anti-programmed cell death 1 (PD-1) or anti-programmed death ligand 1 (PD-L1) antibody therapy is based on an immunohistochemistry (IHC) assessment of PD-L1 expression. Immunological checkpoint inhibitors improve the overall survival of patients with expression of PD-L1; however certain PD-L1-negative patients may also benefit from immunotherapy. This indicates the requirement for novel predictive factors for the qualification of immunot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
(45 reference statements)
1
14
0
2
Order By: Relevance
“…These immunotherapies block the PD-1 checkpoint to enable the immune system to recognize and target cancer cells. There are now multiple antibodies that are raised against anti-PD1 or anti-PD-L1, including Atezolizumab, Avelumab, Durvalumab, Pembrolizumab, and Nivolumab (120).…”
Section: Immune-checkpoint Inhibitorsmentioning
confidence: 99%
“…These immunotherapies block the PD-1 checkpoint to enable the immune system to recognize and target cancer cells. There are now multiple antibodies that are raised against anti-PD1 or anti-PD-L1, including Atezolizumab, Avelumab, Durvalumab, Pembrolizumab, and Nivolumab (120).…”
Section: Immune-checkpoint Inhibitorsmentioning
confidence: 99%
“…In the last 10 years, miRNA have been demonstrated to participate actively in human tumorigenesis [ 35 38 ]. More specifically, studies have found miR-203 to possess tumor-suppressive function by regulating downstream protein-coding genes in gastric cancer, lung cancer, breast cancer and ESCC [ 39 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past 10 years, miRNA had been demonstrated to take an essential part in tumorigenesis [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%